Antimicrobial and antioxidant activities of a macrolichen Usnea pictoides G. Awasthi (Parmeliaceae) - Pavithra G.M, Vinayaka K.S, Rakesh K.N, Syed Junaid, Dileep N, Prashith Kekuda T.R, Saba Siddiqua, Abhishiktha S. Naik (Journal of Applied Pharmaceutical Science, 2013)
Lichens are self-sufficient symbioses between an alga and a fungus. In the present study, we have determined total phenolic content, antimicrobial and antioxidant efficacy of a macrolichen Usnea pictoides G. Awasthi (Parmeliaceae) collected at Mullayanagiri, Western Ghats of Chikmagalur, Karnataka, India. The lichen was powdered and extracted sequentially using solvents of increasing polarity viz., petroleum ether, chloroform, ethyl acetate and methanol. Total phenolic content of solvent extracts was estimated by Folin-Ciocalteau reagent method. Antimicrobial activity of solvent extracts was tested against two bacteria viz., Staphylococcus aureus and Pseudomonas aerugionsa and two fungi viz., Candida albicans and Cryptococcus neoformans by Agar well diffusion assay. Antioxidant activity of solvent extracts was determined by DPPH free radical scavenging assay and Ferric reducing assay. Thin layer chromatogram showed the presence of usnic acid. The total phenolic content was highest in methanol extract followed by ethyl acetate, chloroform and petroleum ether extracts. S. aureus and C. neoformans showed high susceptibility to solvent extracts among bacteria and fungi. A dose dependent scavenging of DPPH radicals by solvent extracts was observed. The scavenging potential of methanol extract was higher than other extracts. In ferric reducing assay, methanol extract showed stronger reducing power than other extracts. Overall, extracts containing high phenolic contents exhibited stronger antioxidant activity. The inhibitory potential of the lichen extracts might be attributed to the presence of usnic acid. The radical scavenging and ferric reducing potential of solvent extracts could be attributed to the phenolic compounds. A positive correlation was observed between total phenolic content and the antioxidant activity of lichen extracts. The lichen U. pictoides can be a potential candidate for the development of bioactive agents.
Keywords: Usnea pictoides, Western Ghats, A